First-Trimester Threatened Abortion: Can Red Blood Cell Distribution Width-Standard Deviation Predict Miscarriage? - Karagun, Sebnem; Dal, Yusuf; Yildiz, Hamza; Karaca, Sefanur Gamze; Nessar, Ahmet Zeki; Coskun, Ayhan (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: The objective of the study was to investigate the predictive value of red blood cell distribution width-standard deviation (RDW-SD) and another complete blood count (CBC) derived blood markers in patients presenting with threatened abortion concerning miscarriage. STUDY DESIGN: This retrospective cross-sectional study included a cohort of 222 women with threatened abortion in the first trimester. The study group consisted of 114 patients who underwent miscarriage, and the control group included 108 pregnant women who delivered at term. The prognostic potential of RDW-SD and other CBC indices, readily obtainable from blood counts at the presentation of threatened abortion, was examined in the context of miscarriage development. The predictive value was calculated using the Receiver Operating Characteristic (ROC) curve. RESULTS: The analysis revealed a statistically significant decline in RDW-SD within the miscarriage cohort compared to the control group. Notably, no statistically significant differences were identified in the neutrophil-lymphocyte ratio (NLR), derived NLR (DNLR), systemic inflammatory immune index (SII), platelet-to-lymphocyte ratio (PLR), and delta neutrophil index (DNI). CONCLUSION: In this study, we found that RDW-SD, as a novel inflammatory mediator may be a useful marker for miscarriage in first trimester bleeding. However, it should be noted that traditional CBC indices, including NLR, DNLR, SII, PLR, and DNI, were found to be unsuitable indicators for miscarriage in threatened abortion.